Gender and the Gothic in the fiction of Edith Wharton - Fedorko, Kathy A., 1947- (University of Alabama Press, 1995)
Using feminist archetypal theory and theory of the female Gothic, Fedorko shows how, in sixteen short stories and six major novels written during four distinct periods of her life, Wharton adopts and adapts Gothic elements as a way to explore the nature of feminine and masculine ways of knowing and being and to dramatize the tension between them. A distinction in her use of the form is that she has both women and men engage in a process of individuation during which they confront the abyss, the threatening and disorienting feminine/maternal. Wharton deconstructs traditional Gothic villains and victims by encouraging the reader to identify with those characters who are willing to assimilate this confrontation with the feminine/maternal into their sense of themselves as women and men. In the novels with Gothic texts Wharton draws multiple parallels between male and female protagonists, indicating the commonalities between women and men and the potential for a fe/male self.